Keragaman dan Distribusi Mangrove Berdasarkan Tipe Substrat di Pesisir Pantai Kampung Syoribo Distrik Numfor Timur Kabupaten Biak Numfor Provinsi Papua - Laurensius Peri Rambu; Ferawati Runtuboi; Frida A. Loinenak (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
One of the mangrove forest area in Numfor Island is the Syoribo Coastal Coast currently the destruction of mangrove ecosystems is increasingly widespread due to the opening of land to be used as residential and development areas so that there is a reduction in the area of mangrove forests. The research was conducted in April 2018 at the Syoribo Village Coastal Coast of East Numfor District of Biak Numfor District of Papua Province. This study aims to analyze the types and distribution of mangroves, Analyze the composition of species and structure of mangrove vegetation (density, frequency, and dominance), Analyze the mangrove habitat is environmental condition affecting mangrove growth, Analyze texture of substrate which is overgrown by mangrove, Analyze the linkage between mangrove density and substrate texture found. The method used in this study is by combination between path method and line method then substrate analysis was conducted in laboratory. The results showed that in the four observation transects in 7 mangroves species were Sonneratia alba, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, Bruguiera cylindrica, Avicennia alba, and Xylocarpus granatum. The highest value index for tree, sapling and seedlings is the highest Bruguiera gymnorrhiza (197,82%), (160,71%), and (166,36%). Environmental conditions that affect mangrove growth are average temperature (27,6 0C – 29,4 0C), Salinity (6 ‰ – 24,3 ‰), Density (0,004 – 0,014), pH (7,12 – 7,57). The texture of the substrate overgrown by mangroves on the Syoribo, East Numfor have substrate criteria are dust silty clay loam, Silt Loam and sandy loam. Modeling the relationship between the density of tree level, spling, and seedling mangroves with substrate using multiple regression shows a close relationship between the two variables.